Intra-Tile Parallelization for Two-Level Perfectly Nested Loops With Non-Uniform Dependences. (28th May 2020) - Abdi Reyhan, Zahra; Lotfi, Shahriar; Isazadeh, Ayaz; Karimpour, Jaber
Abstract: Most important scientific and engineering applications have complex computations or large data. In all these applications, a huge amount of time is consumed by nested loops. Therefore, loops are the main source of the parallelization of scientific and engineering programs. Many parallelizing compilers focus on parallelization of nested loops with uniform dependences, and parallelization of nested loops with non-uniform dependences has not been extensively investigated. This paper addresses the problem of parallelizing two-level nested loops with non-uniform dependences. The aim is to minimize the execution time by improving the load balancing and minimizing the inter-processor communication. We propose a new tiling algorithm, k-StepIntraTiling, using bin packing problem to minimize the execution time. We demonstrate the effectiveness of the proposed method in several experiments. Simulation and experimental results show that the algorithm effectively reduces the total execution time of several benchmarks compared to the other tiling methods.